Effects of Alemtuzumab on (Auto)antigen-Specific Immune Responses - Hilger, Clara; Riedhammer, Christine; Orsó, Evelyn; Weissert, Robert (Frontiers in Immunology, 2020)
Alemtuzumab (anti-CD52 mAb) leads to a long-lasting disease activity suppression in patients with relapsing forms of multiple sclerosis (MS). In this study, we examined the change of the immune cell repertoire and the cellular reactivity after treatment with alemtuzumab. We analyzed the number of IFN-γ-secreting cells in presence of several peptides which had been eluted from the central nervous system (CNS) of MS patients and are possible targets of autoreactive T cells in MS. The patients showed a stabilized disease activity measured in clinical parameters and lesion formation after the treatment. We detected a reduction of the number of IFN-γ-secreting cells in the presence of every tested self-antigen. The number of IFN-γ-secreting cells was also reduced in the presence of non-self-antigens. We also found a clear change in the immune cell repertoire. After an almost complete depletion of all lymphocytes, the cell specificities showed different reconstitution patterns, resulting in different cell fractions. The percentage of CD4+ T-cells was clearly reduced after therapy, whereas the fractions of B-and NK-cells were elevated. When we evaluated the number of IFN-γ-secreting cells in relation to the number of present CD4+ T-cells, we still found a significant reduction. We conclude that the reduction of IFN-γ-secreting cells by alemtuzumab is not only due to a reduction of the CD4+ T-cell- fraction within the peripheral blood mononuclear cell (PBMC) compartment but might also be caused by functional changes or a shift in the distribution of different subtypes in the CD4+ T-cell pool.